Partial Pearson-two (PP2) of quasi newton method for unconstrained optimization - Basheer M. Salih; Khalil K. Abbo; Zeyad M. Abdullah (Tikrit Journal of Pure Science, 2023)
In this paper, we developing new quasi-Newton method for solving unconstrained optimization problems .The nonlinear Quasi-newton methods is widely used in unconstrained optimization[1]. However,. We consider once quasi-Newton which is (Pearson-two) update formula [2], namely, Partial P2. Most of quasi-Newton methods don't always generate a descent search directions, so the descent or sufficient descent condition is usually assumed in the analysis and implementations [3] . Descent property for the suggested method is proved. Finally, the numerical results show that the new method is also very efficient for general unconstrained optimizations [4].